CULTURAL HUMANISM AND THE CHALLENGE OF GLOBAL JUSTICE (2014)
Philosophers of culture assert that culture is at the root of injustice and subversion of the principles of international cooperation; such that a theory of global culture ought to precede any universally valid principle of justice. In political philosophy, major writers on global justice have attempted to develop principles of justice that would apply universally; but these attempts have been largely unsuccessful because they failed to pay sufficient attention to the significant role culture plays in determining the basis of international cooperation. This study, therefore, examined extant positions on global justice and global culture, and proposed Frantz Fanon's cultural humanism as a theory of global culture, with a view to evolving a universally valid principle of justice that will engender a flourishing global order. This study adopted as framework, Fanon's cultural humanism, which states that a universal cultural mix has become a reality, such that a particular culture is neither the basis of any individual or group identity, nor the grounds for treating anyone unjustly. Eight texts in Philosophy of Culture, including three canonical texts by Fanon, The Wretched of the Earth (TWE); Black Skin, White Masks (BSWM); Toward the African Revolution (TAR) and nine in Political Philosophy, were purposively selected because they dealt extensively with global culture, cultural humanism and global justice. Critical analysis was deployed to interrogate the dominant standpoints on global justice, while the method of reconstruction was used to develop the idea of inter-cultural equality, a principle of global justice that derives from cultural humanism. Texts in Political Philosophy (including Global Justice: Seminal Essays), established that major writers on global justice: the exponents of the political conception, who regard the state as the basis of international cooperation and the cosmopolitans, who take the individual as the basic unit of consideration in thinking about global justice, do not take full cognisance of the overriding role cultural beliefs play in determining acceptable principles of international justice. Texts in Philosophy of Culture generally espouse the view that cultural prejudices are at the root of global injustice and that a theory of global justice ought to take cognisance of cultural pluralism. Fanon asserted that universality resides in the decision to recognise and accept the reciprocal relativism of different cultures (TWE, TAR), while setting aside the false claim that any particular culture is the source of the truth (BSWM). Critical reflections revealed that Fanon's cultural humanism advocates the principle of inter-cultural equality which values human well-being and cooperation above cultural differences, while showing that there are no superior or unblemished national cultures. Inter-cultural equality, thus, recognises and overcomes cultural sentiments and prejudices which constitute serious obstacles in the way of realising global justice; and this consequently offers the requisite conditions for inter-cultural equality to engender a flourishing global order. Fanon's cultural humanism generates inter-cultural equality, a universally valid principle of justice that values human cooperation and well-being above cultural differences. This implies that recognising and respecting cultural pluralism is capable of engendering an egalitarian and flourishing global order.